Determinasi Kepemimpinan Kepala Sekolah dan Kompetensi Guru terhadap Motivasi Belajar Siswa Kelas XI di SMK Pratama Widya Mandala Badung - I Gusti Ayu Ika Monika (Edumaspul: Jurnal Pendidikan, 2021)
The purpose of this study was to determine the determination of principal leadership, teacher competence on learning motivation of class XI students at SMK PratamaWidya Mandala Badung. This research is an "ex post facto" research. The sampling technique used in this study was purposive sampling. The population and sample in this study were students of class XI culinary at SMK Pratama Widya Mandala Badung, totaling 72 people. Data analysis techniques in this study used data description analysis, requirements analysis test, hypothesis testing. The analysis requirements test was carried out by the data distribution normality test, the linearity test and the meaning of the regression coefficient, the multicollinearity test, the heteroscedasticity test, and the auto correlation test. The results showed that: (1) there is a significant determination of the principal's leadership on student learning motivation with an effective contribution of 1.44% (2). There is a significant determination of teacher competence on student learning motivation with an Effective Contribution of 1.13%. (3). Taken together, there is a significant determination of principal leadership, teacher competence on student learning motivation with a determination of 10.8%.